Impact of a tailored exercise regimen on physical capacity and plasma proteome profile in post-COVID-19 condition - Chowdhury, Mohammad Mobarak H.; Fontaine, Marie-Noelle; Lord, Sarah-Eve; Quenum, Akouavi Julite Irmine; Limoges, Marc-André; Rioux-Perreault, Christine; Lucier, Jean-François; Cliche, Dominic O.; Levesque, Dominique; Boisvert, François-Michel; Cantin, André M.; Allard-Chamard, Hugues; et al. (Frontiers in Physiology, 2024)
Background Individuals affected by the post-covid condition (PCC) show an increased fatigue and the so-called post-exertion malaise (PEM) that led health professionals to advise against exercise although accumulating evidence indicates the contrary. The goal of this study is to determine the impact of a closely monitored 8-week mixed exercise program on physical capacity, symptoms, fatigue, systemic oxidative stress and plasma proteomic profiles of PCC cases. Methods Twenty-five women and men with PCC were assigned sequentially to exercise (n = 15) and non-exercise (n = 10) groups. Individuals with no PCC served as a control group. The exercise program included cardiovascular and resistance exercises. Physical capacity, physical activity level and the presence of common PCC symptoms were measured before and after the intervention. Fatigue was measured the day following each exercise session. Plasma and PBMC samples were collected at the beginning and end of the training program. Glutathione and deoxyguanosine levels in PBMC and plasma proteomic profiles were evaluated. Results Bicep Curl (+15% vs 4%; p = 0.040) and Sit-to-Stand test (STS-30 (+31% vs +11%; p = 0.043)) showed improvement in the exercise group when compared to the non-exercise group. An interaction effect was also observed for the level of physical activity (p =0.007) with a positive effect of the program on their daily functioning and without any adverse effects on general or post-effort fatigue. After exercise, glutathione levels in PBMCs increased in women but remained unchanged in men. Discernable changes were observed in the plasma proteomics profile with certain proteins involved in inflammatory response decreasing in the exercise group. Conclusions Supervised exercise adapted to the level of fatigue and ability is safe and effective in PCC patients in improving their general physical capacity and wellbeing. Systemic molecular markers that accompany physical improvement can be monitored by analyzing plasma proteomics and markers of oxidative stress. Large-scale studies will help identify promising molecular markers to objectively monitor patient improvement.